2019
DOI: 10.3390/su11020520
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Distribution and Translocation in Rice (Oryza sativa L.) under Different Naturally Seleniferous Soils

Abstract: Selenium (Se) accumulation in plant foods may be providing dietary Se to minimize the health problems related to Se deficiency. In this study, rice plants were cultivated in different naturally seleniferous soils (0.5–1.5 mg Se kg−1). Se concentration in rice plant tissues was analysed, and the distribution and translocation of Se in rice were also studied. The effect of exogenous Se on yield and Se concentration in rice grain was also investigated by spraying Na2SeO3 (15 mg L−1, 15 g ha−1). Results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…Hu et al [43] reported that when adding exogenous selenium to make the soil selenium concentration reach 0.5 and 1.0 mg Se kg −1 , no changes are found in the weight of rice roots, straw and grains. Similar results were reported by Shen et al [14], who confirmed that foliar spraying of NaSeO 3 (0 and 15 mg L −1 ) would almost make no change to the rice yield. However, Zhang et al [44] indicated that while 50 g Se ha −1 of the selenite fertilizer was applied, the rice yield could significantly increase.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Hu et al [43] reported that when adding exogenous selenium to make the soil selenium concentration reach 0.5 and 1.0 mg Se kg −1 , no changes are found in the weight of rice roots, straw and grains. Similar results were reported by Shen et al [14], who confirmed that foliar spraying of NaSeO 3 (0 and 15 mg L −1 ) would almost make no change to the rice yield. However, Zhang et al [44] indicated that while 50 g Se ha −1 of the selenite fertilizer was applied, the rice yield could significantly increase.…”
Section: Discussionsupporting
confidence: 90%
“…The content of N, P and K in the soil, the primary conditions of the experimental site and the variety and management measures could affect the yield of rice [41,42]. However, selenium may have a specific impact on rice yield [8,14,43,44]. For example, Boldrin et al [8] found that the rice yield would not be significantly affected by applying either selenate fertilizer or selenite fertilizer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations